Upaya Penanganan Depresi Siswa dengan Metode Islami - Inez Yuliane; Rochmah Tri Hayuningsih; Madhurika Hanim; Dawud Suhadak (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Experts say that depression is a disorder that focuses on thoughts and feelings, causing sufferers to experience mental disorders. If it lasts for a long time, if they do not immediately get help from experts, it can have negative impacts in the form of losing orientation in life, weakening their physical potential and mental condition, and can even destroy their future, and loses his human identity. It is not uncommon for teenagers to experience depression, who tend to experience stress triggered by personal problems that arise. Islamic-based counseling can overcome adolescent problems including depression. The counseling is tailored to the problems the client is experiencing. There are many cases of teenage depression caused by many factors. The role of educational institutions here is very important to overcome student depression through counseling guidance. Guidance and guidance teachers in schools also need to understand the values of Islamic religiosity. Through Islamic methods, guidance and counseling teachers can provide stimulus and treatment for student depression, the development of treatment in the world of medicine has moved towards a religious approach. Various research results show that a person's level of faith is closely related to their immunity and resistance to various life problems which trigger psychosocial stress. This means that health standards include physical, spiritual, social and spiritual health.